Pascal's Wager: Pragmatic Arguments and Belief in God. By Jeff Jordan - Gould, Graham (The journal of theological studies, 2007)
This study focuses mainly on two forms of Pascal's Wager, which Jordan refers to as the ‘canonical’ and the ‘Jamesian’ versions. The canonical version, so called because it is the form of the Wager most commonly analysed by philosophers, argues that Christian theism should be chosen ahead of atheism because of the potentially infinite utility of belief in God, which, if true, leads to eternal life. The Jamesian Wager, so called after William James, by contrast, includes the proposition that belief in God has this-wordly as well as other-wordly benefits (both to the individual and to society). Jamesian belief thus offers a better outcome than its rivals in all situations, even should belief in God turn out to be false.